Cambridge o Level Physics - Kennet heather; Tom Duncan (London Hodder Education Group, 2021)
This title is endorsed by Cambridge Assessment International Education to support the full syllabus for examination from 2023. Written by renowned expert authors, our updated resources enable the learner to effectively navigate through the content of the revised Cambridge O Level Physics (5054) syllabus for examination from 2023. - Develop strong practical skills: practical skills features provide guidance on key experiments, interpreting experimental data, and evaluating results; supported by practice questions for preparation for practical exams or alternatives. - Build mathematical skills
Keywords: Physics Examinations; Physics Examinations Study guides; Physique Examens Guides de l'étudiant; Study guides